2015
DOI: 10.1016/j.shaw.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic Evaluation of Biomechanical Hand Function

Abstract: The human hand is a complex structure that performs various functions for activities of daily living and occupations. This paper presents a literature review on the methodologies used to evaluate hand functions from a biomechanics standpoint, including anthropometry, kinematics, kinetics, and electromyography (EMG). Anthropometry describes the dimensions and measurements of the hand. Kinematics includes hand movements and the range of motion of finger joints. Kinetics includes hand models for tendon and joint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
41
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 84 publications
4
41
0
2
Order By: Relevance
“…During the rehabilitation processes, therapists assess the active and passive ROM (AROM and PROM, respectively) of hand joints as general indicators of the hand function. 2,3 More recently, the assessment of the functional range of motion (FROM) has been proposed, especially for the wrist, elbow and shoulder. The FROM is defined as the minimum ROM necessary to comfortably and effectively perform ADL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the rehabilitation processes, therapists assess the active and passive ROM (AROM and PROM, respectively) of hand joints as general indicators of the hand function. 2,3 More recently, the assessment of the functional range of motion (FROM) has been proposed, especially for the wrist, elbow and shoulder. The FROM is defined as the minimum ROM necessary to comfortably and effectively perform ADL.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 In addition, the available studies on FROM of hand joints present some deficiencies and limitations. The first deficiency is that none of them analyzes the palmar arching provided by the flexion of the little and ring carpometacarpal (CMC) joints nor the abduction motions of the fingers or thumb, as was also observed in a recent review work, 3 where attention was drawn to the need for further research examining the ROM and hand functions of the thumb, because of its importance in hand function. 14 Abductions of fingers are needed to assure stability when grasping objects with different sizes, as they allow for higher distances between fingertips.…”
Section: Introductionmentioning
confidence: 99%
“…The daily tool operation by hand is not only related to HGS, but is also relevant to GCS, a control ability of force exert accurately by hand palm [4,5]. Numerous studies have aimed to understand the factors related to occupational safety and application, specifically HGS and GCS [6][7][8][9][10][11]. Those studies indicated that hand grip strength was a critical source of power for work-related operations.…”
Section: Introductionmentioning
confidence: 99%
“…There are different approaches to the functional analysis of the hand (Lee & Jung 2015). The methods currently used are focused on three aspects: grip strength evaluation (basically cylindrical and pinch), maximum joint ranges of motion and either the application of tests that evaluate different aspects such as dexterity, eyehand coordination or mobility, or subjective questionnaires about functionality.…”
Section: Introductionmentioning
confidence: 99%